How Effective Are Early Grade Reading Interventions? : A Review of the Evidence - Graham, Jimmy; Kelly, Sean (World Bank, Washington, DC, 2018)
It is imperative that students learn to read in the early grades, yet many fail to do so in developing countries. Early grade reading interventions have emerged as a common means to attempt to address this problem. This paper presents a definition of early grade reading interventions as interventions that employ a combination of five components: at a minimum, they must train teachers to teach reading using simplified instructional techniques and evidence-based curricula. In addition, they typically include in-class coaching and the provision of instructional guidelines, instructional materials, or tools for student assessment. To develop a better understanding of the effectiveness of the interventions, the paper summarizes evidence from 18 early grade reading interventions, occurring across a large variety of contexts, including four World Bank regions and three World Bank income groups. The study finds that early grade reading interventions are consistently effective, although not infallible. The large majority had highly significant impacts on at least one reading subtask. However, only for a few interventions were effect sizes large enough to equate to more than a year's worth of schooling or create fluent readers on average. The cost of implementation varied widely, but some programs were highly cost-effective. Some programs failed to achieve impact altogether, although these programs were in the minority. In short, early grade reading interventions are not a guaranteed means to improve reading, and they rarely lead to fluency over a short span of time, but they are a mostly reliable means to make significant improvements in literacy over a short period of time.